The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.1111/ajad.13386
|View full text |Cite
|
Sign up to set email alerts
|

A longitudinal study on the impact of Internet gaming disorder on self‐perceived health, academic performance, and social life of first‐year college students

Abstract: Background and Objectives Internet gaming disorder (IGD) is associated with health, social, and academic problems but whether these are consequences of the disorder rather than precursors or correlates is unclear. We aimed to evaluate whether IGD in the 1st year of university predicts health, academic and social problems 1 year later, controlling for baseline health, academic and social problems, demographics, and mental health symptoms. Methods In a prospective cohort study, 1741 university students completed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…These specific areas included: 'family'; 'friends'; 'partner'; 'school and/or work'; 'physical health'; and 'psychological health' . These specific types of functional impairments were proposed on the basis of a previous research attesting their relevance and role in disordered gaming (see [32][33][34][35] ).…”
Section: Functional Impairmentsmentioning
confidence: 99%
“…These specific areas included: 'family'; 'friends'; 'partner'; 'school and/or work'; 'physical health'; and 'psychological health' . These specific types of functional impairments were proposed on the basis of a previous research attesting their relevance and role in disordered gaming (see [32][33][34][35] ).…”
Section: Functional Impairmentsmentioning
confidence: 99%
“…The detection of risk personality patterns for IGD could be useful in the design of prevention and treatment programs for gambling disorders. The IGD can negatively affect school or college performance, and cause job loss or marital failure (Benjet et al, 2023;Chattopadhyay et al, 2020;Grzegorzewska, 2017;Pereira et al, 2021). Ji et al (2022) carried out a meta-analysis, in which strong correlations were found between IGD and maladaptive cognitions and motivations that were amenable to therapeutic treatment.…”
Section: 4mentioning
confidence: 99%
“…The results of these studies indicate a significant correlation between the two. [11][12][13][14][15] A review of the literature shows that global aspects of the educational system have been studied locally [16][17][18][19][20] and nationally 21 from the quality of services, motivation, 22 and career destiny 23 mostly from one angle view (i.e., educational perspectives). However, in a cross-discipline view to integrate psychological issues into the educational system, there is still work to do.…”
Section: Introductionmentioning
confidence: 99%